The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1111/j.1748-7692.1999.tb00787.x
|View full text |Cite
|
Sign up to set email alerts
|

DEMOGRAPHY AND BREEDING BIOLOGY OF A SMALL, LOCALIZED POPULATION OF SOUTHERN ELEPHANT SEALS (MIROUNGA LEONINA)

Abstract: Southern elephant seals have been studied in depth in most of their breeding range. One notable exception is the Falkland Islands population. We present data on demography and breeding biology of elephant seals of Sea Lion Island, the main breeding site of this species in the Falklands. Sea Lion Island shelters a small, localized population of southern elephant seals (5 16 breeding females in 1995 and 518 in 1996). Comparison with the few available census data collected prior to our study suggests that the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
1
5

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(94 citation statements)
references
References 45 publications
3
84
1
5
Order By: Relevance
“…Mark-recapture studies have indicated a high proportion of seals showing philopatry, and these studies have not produced any matches between PV and SG (see Lewis et al 1996). However, subadult males have been resighted between PV and the Falkland islands during both moulting and breeding seasons (C. Campagna, unpublished data;Galimberti & Boitani 1999), and this geographically intermediate island could serve as a conduit for dispersal between PV and SG. This is supported by the observation that males (but not females) tagged in SG have been resighted at the Falkland islands.…”
Section: Discussion (A) Genetic Di¡erentiationmentioning
confidence: 99%
“…Mark-recapture studies have indicated a high proportion of seals showing philopatry, and these studies have not produced any matches between PV and SG (see Lewis et al 1996). However, subadult males have been resighted between PV and the Falkland islands during both moulting and breeding seasons (C. Campagna, unpublished data;Galimberti & Boitani 1999), and this geographically intermediate island could serve as a conduit for dispersal between PV and SG. This is supported by the observation that males (but not females) tagged in SG have been resighted at the Falkland islands.…”
Section: Discussion (A) Genetic Di¡erentiationmentioning
confidence: 99%
“…Females first bred at between 4 and 7 years of age (mean at Macquarie Island 5.2 ± 1.8 years) and the estimated annual fecundity rate at South Georgia was 0.391 (Hindell 1991). At Peninsula Valdes, 96% of females that came ashore gave birth, and in the Falkland Islands, 100% (Campagna et al 1993;Galimberti & Boitani 1999). The successful pupping by the 23 year old females seen by Hindell & Little (1988) suggest that there may be no reproductive senescence.…”
Section: Age and Mortalitymentioning
confidence: 99%
“…Across their distribution, the day the maximum number of females is hauled out varies from 2 October at Punta Delgada (42° 30'S) through 18 October at Heard Island (53°00'S) to 25 October at South Georgia (54° 19'S) and King George Island (62° 16'S) (Campagna et al 1993;Galimberti & Boitani 1999). The duration of the parturition period is reasonably consistent across their distribution at close to 60 days, and the number of females ashore approximates a Gaussian model (Hindell & Burton 1987;Galimberti & Boitani 1999). Small females tend to arrive earlier than large females, and the departure date is slightly more irregular than arrival.…”
Section: Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the tourist attractions is the chance of viewing killer whales close to shore. On the eastern side of the island, sandy beaches on the north and south coasts are the site of the largest elephant seal (Mirounga leonina) breeding colony in the Falklands, which produces around 500 pups per year (Galimberti and Boitani, 1999). Reproduction in elephant seals occurs over a three month period, starting in early September on Sea Lion Island with maximum presence on 20 October.…”
Section: Introductionmentioning
confidence: 99%